Endovascular treatment for vaccine-induced cerebral venous sinus thrombosis and thrombocytopenia following ChAdOx1 nCoV-19 vaccination: a report of three cases. (15th November 2021) - Cleaver, Jonathan; Ibitoye, Richard; Morrison, Hamish; Flood, Richard; Crewdson, Kate; Marsh, Aidan; Abhinav, Kumar; Bosnell, Rose; Crossley, Robert; Mortimer, Alex
Abstract : Background: Vaccine-induced thrombosis and thrombocytopenia (VITT) is a rare complication following ChAdOx1 nCoV-19 vaccination. Cerebral venous sinus thrombosis (CVST) is overrepresented in VITT and is often associated with multifocal venous thromboses, concomitant hemorrhage and poor outcomes. Hitherto, endovascular treatments have not been reviewed in VITT-related CVST. Methods: Patient records from a tertiary neurosciences center were reviewed to identify patients who had endovascular treatment for CVST in VITT. Results: Patient records from 1 January 2021 to 20 July 2021 identified three patients who underwent endovascular treatment for CVST in the context of VITT. All were female and the median age was 52 years. The location of the CVST was highly variable. Two-thirds of the patients had multifocal dural sinus thromboses (sigmoid, transverse, straight and superior sagittal) as well as internal jugular vein thromboses. Intracerebral hemorrhage occurred in all patients; subarachnoid blood was noted in two of them, and intraparenchymal hemorrhage occurred in all. There was one periprocedural parenchymal extravasation which abated on temporary cessation of anticoagulation. Outcome data revealed a 90-day modified Rankin Scale (mRS) score of 2 in all cases. Conclusions: We demonstrate that endovascular treatment for VITT-associated CVST is feasible and can be safe in cases that deteriorate despite medical therapy. Extensive clot burden, concomitant hemorrhage, rapid clinical progression and persistent rises in intracranial pressure should initiate multidisciplinary team discussion for endovascular treatment in appropriate cases.